Estratégia para uma melhor contribuição dos PMO para a sustentabilidade empresarial - Campos, Ana Beatriz Borges (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence